Intense Foxp3+CD25+ regulatory T‐cell infiltration is associated with high‐grade cutaneous squamous cell carcinoma and counterbalanced by CD8+/Foxp3+CD25+ ratio. (30th November 2014) - Azzimonti, B.; Zavattaro, E.; Provasi, M.; Vidali, M.; Conca, A.; Catalano, E.; Rimondini, L.; Colombo, E.; Valente, G.
Summary Background Recent reports have revealed the therapeutic potential of cell‐mediated immunity in neoplasms such as cutaneous squamous cell carcinoma (SCC). Objectives To define the antigenic coexpression of regulatory T cells (Tregs) and plasmacytoid dendritic cells (pDCs) and assess the CD8+/Foxp3+CD25+ cell ratio at peritumoral and intratumoral levels in order to investigate a correlation with the aggressiveness of SCC tumours. Methods We evaluated the content and distribution of Foxp3+CD25+ Treg and CD123+ pDC infiltration and assessed CD8+/Foxp3+CD25+ cell ratio at peritumoral and intratumoral levels in 40 SCCs (20 well‐differentiated, G1; and 20 moderately to poorly differentiated, G2–G3) to investigate a correlation with their aggressiveness. We determined the profiles of Tregs and CD123+ cells; immunostained for CD4, CD8, CD123, interleukin (IL)‐1 and transforming growth factor (TGF)‐β1; and unequivocally double stained for Foxp3CD25. Results Peritumorally, CD4, CD8 and Foxp3 expression showed no difference between the two groups. CD123+ cells were fewer in G2–G3 (P = 0·0005), while Foxp3+CD25+ cells were more numerous (P = 0·0005). The Foxp3+CD25+/Foxp3+ ratio was higher in G2–G3 cases (P = 0·0005), confirming the trend in this group of activated T lymphocytes towards total Treg Foxp3+ cells, while the CD8+/Foxp3+CD25+ ratio was higher in G1 (P = 0·0005). Intratumorally, CD4+ and CD8+ cells infiltrated G2–G3 (P = 0·048) more than G1 (P = 0·004), whereas almost all cells were CD123 negative. Regarding Foxp3CD25, TGF‐β1 and IL‐10, they were less expressed in G1, whereas they were positive in G2–G3 (P < 0·05). The CD8+/Foxp3+CD25+ ratio was similar to that observed in peritumoral infiltration. Conclusions Our data suggest that intratumoral recruitment of Tregs, high expression of TGF‐β1 and IL‐10, almost negative CD123+, and a low CD8+/Foxp3+CD25+ T‐cell ratio may contribute to the aggressiveness of cutaneous SCC, as already evidenced for other solid tumours.